KARAKTERISTIK DAN VIABILITAS BIJI GAHARU (Aquilaria microcarpa Baill.) DARI TANAMAN KOLEKSI KEBUN RAYA BOGOR - Wahyuni, Sri (Buletin Kebun Raya, 2008)
The characteristics and viability of agarwood (Aquilaria microcarpa Baill.) seed from the Bogor Botanic Gardens collection was investigated. Two batches of seed from intact mature fruit and dehisced mature fruit were tested for viability using germination and tetrazolium test methods. The result showed that although the tetrazolium test indicated a similar level of seed viability between the two batches (i.e. 85 â 93 %), the germination capacity of seed batch derived from dehisced fru,it was greatly reduced (i.e. 46 % total seed germination) compared to that derived from intact fruit (i.e. 97 % total seed germination). The decrease of seed germination capacity indicated the loss of seed vigour and was concomitant with the decrease of seed moisture content from 42.22 % to 24.79 % (fresh weight basis), thus underlining that the seed has a recalcitrant characteristic. Further observation on the seedling growth showed that there was an incidence of abnormal seedlings encountered in the seed batch from dehisced fruit. Detailed information on the morphological characteristics of the fruit, seed and seedling are presented in this paper.